Rioli on sidelines
tag=1 data=Rioli on sidelines tag=3 data=NT News tag=8 data=MPS BIOGRAPHIES%GAMES tag=9 data=BATHURST ISLAND tag=32 data=RIOLI, MAURICE%RIOLI, GAVIN tag=34 data=PRSS tag=61 data=30 tag=62 data=Jun tag=63 data=2000